Implementasi Manajemen Konflik Terhadap Perilaku Bullying Di Pondok Pesantren Al-Fattah, Jember - Ananda, Dahniar; Nur, Lailiyah; Rifa’i, Samsul; Zuhro’ Fitriana, Ani Qotuz (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
Bullying behavior in the pesantren environment can create an environment that is less supportive of the development of students. Bullying behavior can hurt students, so they feel unwanted and rejected by their environment. This of course will have an effect on the various activities of Islamic boarding school students. The researcher took the title "Implementation of Conflict Management Against Bullying Behavior at Al-Fattah Islamic Boarding School, Jember". With the formulation of the problem studied, namely "Factors that trigger bullying at Al-Fattah Islamic Boarding School, Jember" and "implementation of conflict management on bullying behavior at Al-Fattah Islamic Boarding School, Jember". The author uses a qualitative descriptive research method. Research with this type of case study aims to find out about something in depth. The conclusions of the research results are: (1) The perpetrators of bullying are senior students in Islamic boarding schools who have high temperament and low empathy. (2) Actions taken by caregivers and administrators of Islamic boarding schools, namely trying to understand the situation of Islamic boarding schools and giving mandates to administrators to pay more attention to the students.